Destabilising data: The use of creative data visualisation to generate professional dialogue. (24th October 2020) - Burnett, Cathy; Merchant, Guy; Guest, Ian
Abstract : Whilst there is plenty of debate on the nature and role of data in social science research, data in schools tend to be understood in terms of numbers and used in limited ways linked primarily to attainment. The 'datafication' of schooling has been strongly critiqued for its powerful impacts on policy and practice, pupils' experience, the curriculum, teaching and learning, and —as is particularly relevant to this article—teachers' professional and personal lives. There is a need therefore to expand what counts as data in schools, to think creatively about how data are communicated, and to consider what data do when inserted differently into professional dialogue. In exploring such possibilities and speaking to the field of critical data studies, this article reports on a project that set out to 'do data differently' by inviting teachers to create, visualise and share their own data on what mattered to them in their everyday literacy teaching using a postcard format. Characteristics of teachers' response to this project are explored, linked to: impressionism, imperfection and subjectivity in data collection; complexity and opacity of visualisation; and professional discussion as drift. Rooted in a sociomaterial perspective and drawing on Latour's ideas about immutable mobiles, it is argued that shifting the focus, visualisation and sharing of data can have 'complicating effects' which—through foregrounding the instability and partiality of data—can produce generative spaces for teachers' professional dialogue.